Visual-Enhanced Discovery Learning: An Action Research Study on Improving Natural and Social Sciences Learning Outcomes in Elementary Education - Amelia, Putri; Pendit, Sinta Satria Dewi; Wilade, Surahman; Firmansyah, Arif; Isnayanti, Andi Nur (Journal of Innovation and Research in Primary Education, 2025)
Learning outcomes in Natural and Social Sciences (IPAS) among elementary students remain suboptimal due to traditional teacher-centered approaches that limit active engagement and conceptual understanding. This study investigated the effectiveness of discovery learning models assisted by image media in improving fourth-grade IPAS learning outcomes. A classroom action research design following Kemmis and McTaggart's cyclical model was implemented over two cycles at SDN 8 Mamboro with 29 fourth-grade students. Data collection employed achievement tests validated by experts (content validity ratio = 0.85, Cronbach's alpha = 0.82) and structured observations. Each cycle comprised planning, action, observation, and reflection phases, with discovery learning activities supported by curriculum-aligned image media. The intervention demonstrated progressive improvements across cycles. Pre-intervention baseline showed 42.5% student competency, increasing to 69.0% in Cycle I and achieving 100% competency in Cycle II. Classical absorption rates improved from 42.5% baseline to 61.75% in Cycle I and 90.75% in Cycle II. Student engagement levels increased from 75% to 88.75%, while teacher effectiveness scores improved from 83.75% to 90%. All students achieved minimum competency standards by the final cycle, with scores ranging from 75-100. The findings validate constructivist learning principles and demonstrate the synergistic effects of combining discovery learning with visual media. Results align with previous research on student-centered approaches while extending understanding of multimedia integration in elementary science education. The dramatic improvement from passive to active learning confirms the effectiveness of this pedagogical combination in addressing contemporary educational challenges and supporting diverse learning styles in IPAS instruction.